Study Penerapan Standar: Kebijakan Pemerintah Tentang Penghasilan Yang Diperoleh Sektor UMKM - -, Muh. Farhan; Faidul Adzim; Abdul Haris Pelu; Baso Syahrul Ramadan; Zainal Furkan; Nurul Mumtazah Simpajo (Indonesian Journal of Research in Economy, 2022)
Micro, Small and Medium Enterprises (MSMEs) play an important role in supporting community welfare. The government has taken steps to pay special attention to MSMEs and support economic growth by issuing Government Regulation (PP) Number 46 of 2013, especially for businesses with revenues below IDR 4.8 billion. The PP, which came into effect on July 1 2018, aims to assist the public in paying business taxes by implementing a final Income Tax (PPh) of 1% of the turnover obtained. Based on the researcher's analysis, the two regulations are similar in many general ways. However, the significant difference lies in the latest tax rates which came into effect on July 1 2018. In this revision, the corporate income tax rate on gross income was changed to 0.5%, replacing the previous rate of 1%, which had been in effect since 2018. 2013. Therefore, the government revised the tax rate rules for MSMEs from Government Regulation Number 46 of 2013 to Government Regulation Number 23 of 2018 with the latest rate of 0.5%. These two regulations are final, which means the calculations are based directly on the gross amount. Tax payments can be made via Electronic Deposit Letter (SSE), and after payment is made, it is considered that you have reported your tax without needing to report it back to the tax office or through other applications. By applying a rate of 0.5%, it is hoped that taxpayers, including PT Bisnis Teknologi Management, will continue to comply with their obligations in reporting taxes.